Trinity Long Room Hub Arts and Humanities Research Institute Annual Report 2023-24 - Curtis, Caitriona; Held, Rike; Johnson, Emily; King, Aoife (Trinity College Dublin, 2024)
The Trinity Long Room Hub Arts and Humanities Research Institute is dedicated to advancing Trinity College Dublin’s internationally recognised research in the Arts and Humanities. Our mission is to stimulate and support the work of our community on an individual, collaborative, and interdisciplinary basis. We seek to maintain the integrity of independent and cutting-edge scholarship while developing and pioneering collaborative interdisciplinary research projects. We engage with diverse audiences and partners through debates, seminars, research projects, lectures, and a wide range of public events to advance the impact of Trinity’s Arts and Humanities and contribute to shaping national and international research agendas. This annual report covers the activities and achievements of the institute during the 2023-24 academic year.
PUBLISHED
Public policy relevance in this report includes but is not limited to the launch of the first national guidelines on Open Access Publishing, in partnership with the Royal Irish Academy as part of the NORF funded PublishOA.ie project; the launch of the Enterprise Ireland funded AI:OK initiative by Trinity Long Room Hub Policy Fellow Martin Clancy to identify ethical music products and services in the age of AI; research by VRF Prof Van Gosse on racism in Irish public discourse; the EU Marie Sklodowska Curie co-funded Human+ project featuring in a 2023 Finnish Impact Foundation white paper on the `State of industry-academia collaboration in humanities, arts and social sciences.
Keywords: Arts and Humanities; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Making Ireland; Manuscript, Book and Print Cultures; Arts and Humanities Policy